2015
DOI: 10.1186/s13046-015-0209-7
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-195 suppresses tumor cell proliferation and metastasis by directly targeting BCOX1 in prostate carcinoma

Abstract: Elucidation of the downstream targets regulated by the metastasis-suppressive miRNAs can shed light on the metastatic processes in prostate cancer (PCa). We conducted microarray analyses and found that miR-195 was significantly decreased in metastatic PCa. Low miR-195 expression is an independent prognostic factor for poor biochemical recurrence-free and overall survival. Forced expression of miR-195 in PCa cells drastically inhibits proliferation, migration and invasion in vitro and inhibits tumor growth and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 44 publications
1
37
1
Order By: Relevance
“…MiR-195 is a member of the miR-15/16/195/424/497 family [24]. It has been reported that miR-195 suppresses cancer development and is downregulated in multiple types of cancer, such as prostate [25, 26], lung [27], osteosarcoma [28], HCCs [29], and so forth. Genome-wide screening suggests that miR-195 mediates NF-κB activity by directly targeting the expression of IKKα TAB3 in HCCs [19].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-195 is a member of the miR-15/16/195/424/497 family [24]. It has been reported that miR-195 suppresses cancer development and is downregulated in multiple types of cancer, such as prostate [25, 26], lung [27], osteosarcoma [28], HCCs [29], and so forth. Genome-wide screening suggests that miR-195 mediates NF-κB activity by directly targeting the expression of IKKα TAB3 in HCCs [19].…”
Section: Discussionmentioning
confidence: 99%
“…This family is comprised of six members and clustered on three separate chromosomes (Porrello et al, ). Recently, several studies in cancer cell lines and tumor samples have demonstrated the down‐regulation of miR‐195‐5p in prostate cancer (Cai et al, ; Guo et al, ; Wu et al, ), lung cancer (Yongchun et al, ; Liu et al, ), breast cancer (Zhao et al, ; Singh et al, ), hepatocellular carcinoma (Qu et al, ; Xu et al, ), and osteosarcoma (Han et al, ). Given that miR‐195‐5p has been reported to be frequently downregulated in cancer and tumor cell lines, we supposed that miR‐195‐5p may function as a tumor suppressor in osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…miR‐195‐5p , which belongs to miR‐16/15/195/424/497 family, is regularly downregulated in numerous types of tumors, including prostate cancer (Cai et al, ; Guo et al, ; Wu et al, ), lung cancer (Yongchun et al, ; Liu et al, ), breast cancer (Zhao et al, ; Singh et al, ), hepatocellular carcinoma (Qu et al, ; Xu et al, ), and osteosarcoma (Han et al, ). Studies in tumor cell lines and tumor samples have shown that miR‐195‐5p could inhibit cell proliferation, invasion, and metastasis through regulating multiple target genes, thus functions as a tumor suppressor (Cai et al, ; Han et al, ; Liu et al, ; Wu et al, ; Xu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have indicated that miR-93, miR-195, and members of the let-7 family of miRs are downregulated in lung cancer, CRC, and melanoma tissues as compared with normal tissue, suggesting that these miRs are tumor suppressors [29][30][31][32][33][34][35][36][37]. miR-93 can suppress the proliferation of human colon cancer cells and colon cancer stem cells, with worse OS being associated with low miR-93 expression in CRC patients [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…miR-93 can suppress the proliferation of human colon cancer cells and colon cancer stem cells, with worse OS being associated with low miR-93 expression in CRC patients [37,38]. miR-195 can suppress tumor cell proliferation and metastasis by targeting several proteins, including BCOX1, BCL-2, and CARMA3 [32][33][34]. The overexpression of let-7b in vitro can downregulate cell-cycle-related proteins, including cyclin D1, cyclin D3, cyclin-dependent kinase 4, and the high-mobility group protein and oncogene [30,39].…”
Section: Discussionmentioning
confidence: 99%